2010
DOI: 10.1111/j.1468-1293.2010.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Detecting impaired glucose tolerance or type 2 diabetes mellitus by means of an oral glucose tolerance test in HIV-infected patients

Abstract: ObjectiveAs a proactive diagnosis of diabetes mellitus (DM) may prevent the onset of severe complications, we used an oral glucose tolerance test (OGTT) to check for impaired glucose tolerance (IGT) and DM in patients with long-standing HIV infection and long durations of exposure to antiretroviral drugs with normal fasting plasma glucose (FPG) levels. MethodsThis was a cross-sectional, single-centre study. The homeostatic model assessment for insulin resistance (HOMA-IR) and 2-h post-load glucose levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
(77 reference statements)
4
16
1
Order By: Relevance
“…Unlike previous studies, 18,20,48,62,63 we did not find an association between BMI, CD4 + cell count, or HIV viral load and rates of DM. Our study population had lower BMI and baseline CD4 + count (Table 1), which may have limited our ability to detect an association between these variables and DM or IFG.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike previous studies, 18,20,48,62,63 we did not find an association between BMI, CD4 + cell count, or HIV viral load and rates of DM. Our study population had lower BMI and baseline CD4 + count (Table 1), which may have limited our ability to detect an association between these variables and DM or IFG.…”
Section: Discussioncontrasting
confidence: 99%
“…The association of CD4 count with diabetes suggests that immune impairment resulting from HIV infection may magnify the risk of glucose dysregulation. Low CD4 count has previously been associated with diabetes in HIV-infected individuals [41] and helps explain the links between infectious and non-communicable diseases. Physical activity greater than 600 metabolic equivalents per week and an upper tertile of handgrip strength in our study were associated with reduced risk of diabetes.…”
Section: Plos Onementioning
confidence: 86%
“…Studies exploring the associations of CD4 cell count with abnormal glucose levels in HIV patients show inconsistent results. Low CD4 cell count was associated with IGT and DM in patients co-infected with HIV, hepatitis C and hepatitis B virus [67]. El-Sadr et al reported an inverse relationship between CD4 counts and insulin resistance in HIV patients, but no relationship between CD4 counts and fasting glucose concentrations [2].…”
Section: Mechanismsmentioning
confidence: 99%
“…HbA1c should not be used for diagnostic purposes in HIV patients as it may underestimate glycemia, especially among patients on NRTIs; this may be a result of NRTI-induced macrocytosis [102]. Additionally, the oral glucose tolerance test may be used to detect IGT or DM in selected HIV patients who have a normal fasting glucose [67]. …”
Section: Screening and Diagnosismentioning
confidence: 99%